THE THERAPEUTIC TREATMENT OF PEPITEM INCREASES THE PROTEIN EXPRESSION OF SIRT1 IN A MOUSE MODEL OF EXPERIMENTAL AUTOIMMUNE ENCEPHALOMYELITIS (EAE) AS A MODEL FOR HUMAN MS - Alassiri, Mohammed (LIFE: International Journal of Health and Life-Sciences, 2024)
Objective: To investigate the effect of the prophylactic and therapeutic treatment of the immunopeptide PEPITEM on the protein expression of SIRT1 in a mouse model of experimental autoimmune encephalomyelitis (EAE) as a model for human MS. Methods: Using C57BL/6 female mice, we dosed the PEPITEM in the EAE model via intraperitoneal injections either prophylactically or therapeutically. The disease was induced using MOG35-55 and complete Freund's adjuvants augmented with pertussis toxin. The EAE score was recorded daily until the end of the experiment (21 days). A Western blot analysis was performed on the brain lysate to measure the protein concentration of SIRT1. Results: The therapeutic treatment with PEPITEM increased the protein expressions of SIRT1 on the EAE mice whereas the prophylactic injections did not affect the protein expression of SIRT1. Conclusion: Collectively, the therapeutic treatment with PEPITEM suggesting anti-inflammatory effect of PEPITEM on the brain damage in EAE mice which offers a novel and safe strategy for drug therapy in MS, opening new avenues for research and treatment.